Meta-analysis of perceptions of occupational risks in the COVID-19 era - Cruz Garcia Lirios (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The objective of the work was to review the literature on the perception of occupational risks during the pandemic. A documentary, cross-sectional and systematic research was carried out with a selection of journals indexed to international repositories, considering the period that the pandemic takes from 2019 to 2022. A network of profusion and connectivity was found that explains the differences and perceptive similarities around risks labor. In relation to biosafety policies, it is recommended to adjust the model in order to anticipate decisions and behaviors determined by expectations against or in favor of work accidents and professional illnesses.